Pengembangan Budaya dan Iklim Sekolah Berbasis Kurikulum Merdeka Belajar - Ningsih, Dewi; Patimah, Siti; Subandi, Subandi; Makbulloh, Deden (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
Learning is a profound activity in human life, fostering lifelong knowledge growth. Formal education in schools serves as the primary arena for this learning activity. The curriculum, as a guide for learning, is directed by the Ministry of Education and Culture in Indonesia. This research aims to explore the impact of the Merdeka Belajar curriculum on school culture and climate. Using a qualitative approach and descriptive method, the study analyzes relevant scholarly literature. The findings highlight significant changes in school culture toward a holistic and inclusive approach, accommodating diverse talents and interests of students. The Merdeka Belajar curriculum also influences the school climate by introducing flexibility in subject selection, altering behavioral patterns within it. This research contributes to understanding the impact of the Merdeka Belajar curriculum in transforming the dynamics of school culture and climate in Indonesia.